One-pot method for preparing hydrophilic phytosterol/stanol derivative - HE WENSEN; WANG HUIHUI; ZHANG YILU; CUI DANDAN; LIU YU (2017)
The invention discloses a one-pot method for preparing a hydrophilic phytosterol/stanol derivative, and belongs to the technical fields of food, cosmetics, medicine and chemical engineering. Phytosterol/stanol and diacid or diacid anhydride react for a period of time under the action of ionic liquid to generate the high-purity intermediate product phytosterol/stanol diacid monoester; a hydrophilic modifier is directly added to the reaction system for further reaction without separating the intermediate product, so that a high-purity hydrophilic phytosterol/stanol derivative is prepared. The hydrophilic phytosterol/stanol derivative with purity over 95% can be obtained through extraction separation. The two phases of esterification reaction are conducted in one pot, technological operation is simple, usage and separation of a solvent are reduced, the technological process is short, and energy consumption is reduced. The obtained hydrophilic phytosterol/stanol derivative is high in purity, high in yield and low